Implementation Of Green Human Resource Management In Improving Green Brand Image: The Role of Environmental Behavior As A Moderating Variable - Soni Suardi; Muhamad Risal Tawil; Muhammad Faizul Husnayain; Tono Wartono; Darmun (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
This study aims to analyze the volatility dynamics and spillover phenomena among major crypto assets (Bitcoin, Solana, and Ethereum) and their relationship with the Jakarta Composite Index (JCI), a proxy for the Indonesian capital market. In the era of digital financial integration, the link between speculative crypto asset markets and conventional stock markets is a crucial issue for financial system stability. This study uses daily price time series data for the period 2020-2025. The analysis was conducted using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model and the Diebold-Yilmaz spillover index approach to measure the magnitude of shock transmission between markets. The results indicate significant volatility transmission between the three crypto assets, with Bitcoin remaining the primary volatility transmitter. Furthermore, this study finds an increasing dynamic correlation between the global crypto market and the Indonesian capital market during periods of economic uncertainty. These findings have important implications for investors in portfolio diversification strategies and for Indonesian regulators in monitoring systemic risks originating from digital assets.